STUDENTS’ NEEDS ON THE PROCESS-GENRE MODEL OF TEACHING ESSAY WRITING - Refnald Refnald (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2015)
A good learning model is a model developed based on the analysis of learning needs and feasibility. There are many instructional models proposed by the instructional designer but it is not a guarantee that those models are suitable with the characteristics of the course. This article discusses the students’ needs on the process-genre based model for teaching essay writing. This study was a survey research conducted at the English Language Teaching Study Program of State University of Padang. The data of the study were obtained from students’ responses on the questionnaires regarding the students’ needs on learning essay writing. The re-sults of the study show that (1) there are some explanation and examples that should be considered as the input in teaching and learning process, (2) students need to be able to develop a wide variety of text types, (3) students need to learn different topics of essay writing so that they can enrich their world knowledge, and (4) students need the appropriate tasks/activities that directly help improve their knowledge and skills in developing various text types. Thus the appropriate need analysis can be used effectively in developing a process-genre model for teaching essay writing. Keywords: Teaching Model, Multimedia, Need Analysis, Sociolinguistics